Educação bilíngue de/com surdos: deslocamentos pedagógicos de professores bilíngues como processo de minoração educativa. - Bonfim, Tatiane Cristina (2024)
The education of deaf individuals in Brazil faces historical and structural challenges that hinder the full inclusion and appreciation of the cultural and linguistic specificities of this community. The National Common Curricular Base (BNCC), along with other educational policies, has favored an approach centered on oral language and an educational structure designed for hearing students, perpetuating an inclusion model that often fails to address the real specificities of deaf students. This scenario calls for a critical reassessment and the consolidation of Marginal Pedagogical Practices and Processes of Minoration, which promote singularity and difference, recognizing Brazilian Sign Language (Libras) as the primary language. This thesis aimed to: map the Pedagogical Practices of Bilingual Teachers, highlighting Marginal and Minoration Displacements. To achieve this goal, we shared daily knowledge derived from Bilingual Teachers in the Early Years of Elementary Education (1st to 5th grade), foundational years for building knowledge conveyed in/by and through Libras. The thesis argues that education embracing differences is only realized through Processes of Minoration, which entail Displacements from the normalizing Educational Practices focused on hearing students. However, two types of Pedagogical Displacements are observed: a less radical one, characterized by Marginal Teaching, marked by curricular adaptation practices that still preserve elements of a majoritarian logic; and a more radical one, constituted by Processes of Minoration, which emphasize the presence of difference and the emergence of a creative act, wherein deaf teachers and students create unique modes of pedagogical existence. This second Displacement affirms difference in its productive nature, creating fissures in the homogeneity of educational practices and enabling singularizations. Methodologically, the thesis employed Conversation Circles as a central strategy, emphasizing their flexible and affective approach in discursive interactions. The Circles were conducted in the first semester of 2023 and held virtually via Google Meet and Classroom, as these tools provide interactivity and remote access, enabling the participation of Bilingual Teachers from various municipalities in the state of São Paulo, which would be unfeasible in in-person meetings. These platforms allowed for the use of cameras, microphones, and PowerPoint presentations, as well as the storage of supplementary materials, such as articles, teaching plans, and legislation. The recordings of the meetings facilitated data collection. Collaborators were selected through convenience sampling. The data were analyzed based on two principles: the theoretical-philosophical principle of French Discourse Analysis (FDA) and the Principle of Cartography of Marginal Pedagogical Practices and Processes of Minoration. The results highlighted three distinct movements carried out by Bilingual Teachers: 1-Remaining the same – surrendering to the State Apparatus, remaining “attached” to the Molar Lines of Radical Inclusive Education; 2- Marginalizing – attempting to escape the central logic of in/exclusion through Marginal Pedagogical Practices; 3- Minoring – Pedagogical Displacement in Lines of Flight actions indicating potential Processes of Minoration. I hope that the results presented can contribute to the realization of Bilingual Education of/with/for Deaf individuals and to research in the field of Deaf Studies.